2018
DOI: 10.29299/kefad.2018.19.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Creative Drama on Pre-service Teachers’ Communication Skills

Abstract: Bu araştırmada, yaratıcı drama yönteminin öğretmen adaylarının iletişim becerilerine etkisinin incelenmesi amaçlanmıştır. Deneysel bir çalışma olarak tasarlanan araştırmada zayıf deneysel desenlerden "tek grup öntestsontest desen" kullanılmıştır. Araştırmanın verileri "İletişim Becerileri Ölçeği" ile toplanmıştır. Çalışma grubu 2015-2016 öğretim yılı bahar dönemi, Dumlupınar Üniversitesi Eğitim Fakültesi Türkçe Eğitimi Ana Bilim Dalı 2. sınıfta öğrenim gören ve Etkili İletişim dersini alan 47 öğretmen adayında… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It has been observed that the necessity of students to be active in this process increases participation (Athiemoolam, 2013). Previous studies investigating the effects of drama on pre-service teachers show that drama has positive effects on several skills of pre-service teachers including social skills (Afacan & Turan, 2012;Arslan, Erbay & Saygın, 2010;Aydın Şengül & Topçuoğlu Ünal, 2018;Kara & Çam, 2007;Kılıçaslan & Yayla, 2018;Kocayoruk, 2000). Önalan Akfırat ( 2006) suggested that drama is useful in teaching pre-service teachers the necessary social skills for their profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been observed that the necessity of students to be active in this process increases participation (Athiemoolam, 2013). Previous studies investigating the effects of drama on pre-service teachers show that drama has positive effects on several skills of pre-service teachers including social skills (Afacan & Turan, 2012;Arslan, Erbay & Saygın, 2010;Aydın Şengül & Topçuoğlu Ünal, 2018;Kara & Çam, 2007;Kılıçaslan & Yayla, 2018;Kocayoruk, 2000). Önalan Akfırat ( 2006) suggested that drama is useful in teaching pre-service teachers the necessary social skills for their profession.…”
Section: Literature Reviewmentioning
confidence: 99%